SAT0234 Valvular heart disease in antiphospholipid syndrome. (23rd January 2014) - Saurit, V.; Lema, L.R.; Alvarellos, A.J.; Tibaldi, M.; Coll, M.; Sala, J.; Balestrini, C.; Serra, C.
Abstract : Background: Antiphospholipid syndrome (APS) is defined by the presence of venous or arterial thrombosis, recurrent pregnancy loss and anti-phospholipid antibodies (aPLs). Echocardiographic studies have disclosed heart valve abnormalities in about a third of patients with primary APS, most commonly affecting valve is the mitral valve, followed by the aortic and tricuspid.Valvular lesions (VL) associated with APS are associated with valve dysfunction, predominantely regurgitation; stenosis is less frequent.Valvular involvement usually does not cause clinical valvular disease, but increases the risk for thromboembolic complications, mainly cerebrovascular. Objectives: 1- To study the prevalence of (VL) in APS patients bytwo-dimensional and Doppler echocardiography. 2- To study the frequency of thrombotic lesions 3- Correlate these findings with other clinical features of APS Methods: Sixty six patients from a cardiologist clinic with diagnosis of APS (Sapporo/Sidney classification criteria) between March 2001 and July 2011 were prospectively studied. 50 (76%) were women. Average age 41.5 y.o (range 17-73). 26/66 (39.3%) patients had only obstetric APS, 24/66 (36.3%) had arterial thrombosis and 16/66 (24.2%) had venous thrombosis at the time of APS diagnosis. Mean follow up was 49, 4 months, range (12-135). Statistical analysis was made using INFOSTAT software version 2010. Results: The prevalence of VL was 27/66 (40.9%), 21/27 (77.7%) had mitral valve regurgitation, 4/27 (14.8%) had mitral valve thickness and 2/27 (7.4%) had Aortic insufficiency.The clinical features related with VL were arterial thrombosis (18 vs 6) p=0.0001, hypertension (16 vs 4) p=0.0001, Thrombocytopenia (13 vs 1) p=0.0001, Hyperfibrinogenemia (14 vs 2) p=0.0001, Dyslipidemia (16 vs 6) p=0.02 and livedo reticularis (9 vs 2) p=0.002. In the follow, 17 patients had recurrence of thrombosis 15/17 (88.2%) had VL p=0.0001 Conclusions: The prevalence of VL was 40.9% and it was related with arterial thrombosis, hypertension, thrombocytopenia, hyperfibrinogenemia, dyslipidemia, livedo reticularis and recurrence of thrombosis References: Maksimowicz-McKinnon K, Mandell BF. Understanding valvular heart disease in patients with systemic autoimmune diseases. Cleve Clin J Med. 2004 Nov;71(11):881-5. Review. Petri MA. Classification criteria for antiphospholipid syndrome: the case for cardiac valvular disease. J Rheumatol. 2004 Dec;31(12):2329-30. Tomcsányi J, Zsoldos A, Szabό M.Mitral and tricuspid valve thrombus in antiphospholipid syndrome.Heart. 2004 Jun;90(6):620 Disclosure of Interest: None Declared